The Use of Hydroxyethyl Starch and Crystalloid Solutions during Off-Pump Coronary Artery Bypass Grafting Surgery - A. P. Mazur; P. V. Gurin (Ukrainian Journal of Cardiovascular Surgery, 2016)
The article presents the experience of using of hydroxyethyl starch solutions (HES) during off-pump coronary artery bypass grafting surgery (CABG). A comparative analysis of the use of HES solution with other races crystalloid target. Analyzed the efficacy and safety of this solutions during elective off-pump cabg.